Pengembangan Aplikasi Multimedia untuk Edukasi Sejarah pada Zaman Megalitikum Di Indonesia pada Platform Mobile - Ihsan, Aminuddin; Yuniarti, Rezki; Ilyas, Ridwan (Institut Teknologi Garut, 2025)
This research developed a two-dimensional (2D) educational game themed on the history of the Megalithic Age in Indonesia for mobile platforms using the Rapid Prototyping method and Unity Engine. The aim was to provide interactive learning media that combines historical narratives with exploration-based game mechanics and puzzle solving. The development process included visual asset design, prototyping, and alpha and beta testing. Beta testing involved 20 respondents from junior high and high school levels, resulting in a satisfaction rate of 71.5% (Agree category) based on the Likert Scale, which indicates positive acceptance of the gameplay and educational content. The limitations of the study include the scope of historical material, which only covers the early Megalithic period, the limited number of respondents, and the difficulty level adjustment, which is not yet optimal for all age groups. Further development is recommended to expand the variety of missions, enrich historical content with the latest research references, and add analytical features to monitor user learning achievements.